Evaluation Of Spatial Factors’ Impact On Physical Integration Of Informal Settlements: Erbil City – Iraq - Mawlan, Kayfi Akram (2018)
This thesis studies one of the distinct topics of the urban environment in cities which discusses the integration of urban areas through the spatial dimension. The integration of informal settlements considers all dimensions of the urban development such as social, economic, and spatial. This study focuses on the spatial integration of these settlements. This research is concerned with how to achieve sustainable urban environment in developing cities by investigating the integration of informal settlements on the basis of the impact of spatial aspects. The objectives of this research are to identify and specify key spatial factors that influence the physical integration of informal settlements in the urban fabric of Erbil city, to determine the physical integration within the informal study area and with surrounding neighborhoods, and to determine the most influential spatial factors on the integration of the informal settlements.